Factors affecting good agricultural practice in pineapple farming in Thailand - T. Sriwichailamphan (2018)
This study seeks to investigate factors affecting Good Agricultural Practice (GAP) in pineapple farming in Thailand. A logit model is applied to a sample of 350 growers. This study found that average farm price, a contract with buying companies, age, average yield, being a progressive farmer, food safety and the food standard requirements of the importing countries, and the farmer's own environmental concern influenced adoption. The results suggest that price incentives as well as price stability and market certainty via contract farming are effective policy measures. To accelerate adoption of GAP, appropriate strategies to enhance growers' concern are strongly recommended.